Volumetric reduction of brain metastases after stereotactic radiotherapy: Prognostic factors and effect on local control. (10th May 2022) - Kanayama, Naoyuki; Ikawa, Toshiki; Ohira, Shingo; Hirata, Takero; Morimoto, Masahiro; Ogawa, Kazuhiko; Teshima, Teruki; Konishi, Koji
Abstract: Background and Purpose: Few reports include volumetric measurements as endpoints after stereotactic radiotherapy (SRT) despite the importance of such measurements. This study aimed to (1) investigate the impact of the volumetric response (specifically, an over 65% and over 90% volume reduction in brain metastases) at 6 months post‐SRT on local control and (2) identify the predictive factors for a volumetric response of over 65% and over 90%. Materials and Methods: This study included 250 unresected brain metastases (>0.3 cc) treated with SRT. Doses were stratified according to the biological effective dose (BED). The BED was calculated using four models: linear‐quadratic (LQ): α/β = 10; LQ: α/β = 20; LQ cubic: α/β = 12; and LQ linear: α/β = 10. The median prescription dose was 30 Gy/3 fractions (BED20, 45). The median follow‐up time after SRT was 18.6 months (range, 6.4–81.8 months). Results: In the multivariate analysis, over 65% volume reduction and over 90% volume reduction were prognostic factors for local control (hazard ratio: 2.370, p  = 0.011 and hazard ratio: 3.161, p  = 0.014, respectively). A dose of 80% of the gross tumor volume (GTV) D80 > BED20 58 was a predictive factor for over 65% and over 90% volume reductions (odds ratio: 1.975, p  = 0.023; odds ratio: 3.204, p  < 0.001, respectively). Conclusion: Robust volume reduction of brain metastases at 6 months post‐SRT can predict local control. GTV D80 in the LQ model: α/β = 20 may be warranted for good volume reduction. Abstract : Over 65% and over 90% volume reduction of brain metastases at 6 months post‐SRT predicts good local control. Beneficial volume reduction may require increasing the dose to GTV D80 in the LQ model: α/β = 20, and inhomogeneous dose distribution may be required for SRT for brain metastases.